Корпоративная стратегия развития холдингов нефтяной и газовой промышленности России (Путеводитель предпринимателя, 2020)
The article deals with theoretical aspects of the formation of corporate strategy in the improvement of management holdings of oil and gas industry in accordance with the development and modern requirements for theformation of the financial statements.